Mitochondrial diseases: Drosophila melanogaster as a model to evaluate potential therapeutics. (June 2015) - Foriel, Sarah; Willems, Peter; Smeitink, Jan; Schenck, Annette; Beyrath, Julien
Abstract: While often presented as a single entity, mitochondrial diseases comprise a wide range of clinical, biochemical and genetic heterogeneous disorders. Among them, defects in the process of oxidative phosphorylation are the most prevalent. Despite intense research efforts, patients are still without effective treatment. An important part of the development of new therapeutics relies on predictive models of the pathology in order to assess their therapeutic potential. Since mitochondrial diseases are a heterogeneous group of progressive multisystemic disorders that can affect any organ at any time, the development of various in vivo models for the different diseases-associated genes defects will accelerate the search for effective therapeutics. Here, we review existing Drosophila melanogaster models for mitochondrial diseases, with a focus on alterations in oxidative phosphorylation, and discuss the potential of this powerful model organism in the process of drug target discovery. This article is part of a Directed Issue entitled: Energy Metabolism Disorders and Therapies.